The value of exosomes suppressor of cytokine signaling 1， speckled protein 140 and calcyclin binding protein expressions in peritoneal dialysis effluent in the diagnosis of peritoneal fibrosis - Han Xiao-li; Wang Jia-wei; Wei Zhi-feng; Wang Lin-lin; Guo Bao-zhu; Cao Yan-chun; Jin Yu-jie; Liu Sheng-jun (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the value of suppressor of cytokine signaling 1 （SOCS1）， speckled protein 140 （SP140）， calcyclin binding protein （CacyBP） expressions in peritoneal dialysis effluent in the diagnosis of peritoneal fibrosis （PF）.MethodsA total of 90 patients with end-stage renal disease who underwent peritoneal dialysis in the First Affiliated Hospital of Hebei North University from November 1， 2021 to September 30， 2023 were selected as study subjects. They were divided into PF group （n=38） and control group （non-PF， n=52） according to peritoneal tissue biopsy. The mRNA levels of exsome SOCS1， SP140 and CacyBP in peritoneal dialysis effluent were detected by quantitative reverse transcriptase polymerase chain reaction （qRT-PCR）. The ultrafiltration volume at 4 h， 4 h dialysate/plasma creatinine （4 h D/PCr）， and the ratio of glucose content in dialysate at 4 h and 0 h （D/D0） were detected by peritoneal balance test. The diagnostic value of SOCS1， SP140 and CacyBP expressions in PF was analyzed.ResultsThe mRNA levels of exosomes SOCS1 ［（0.84 ± 0.11） vs （1.00 ± 0.15）］， SP140 ［（0.82 ± 0.12） vs （1.00 ± 0.13）］ and CacyBP ［（0.85 ± 0.09） vs （1.00 ± 0.13）］ in peritoneal dialysis effluent of PF group were significantly lower than those of control group （P<0.05）. In both the PF group， and control group， the mRNA expression levels of exosomes SOCS1， SP140 and CacyBP in peritoneal dialysis effluent were positively correlated with 4 h ultrafiltration dose， and 4 h D/PCr， and negatively correlated with D/D0 （P<0.05）. The expression levels of SOCS1， SP140 and CacyBP had diagnostic value in PF. The area under the curve （AUC） of the combined diagnosis of SOCS1， SP140 and CACYBP was the largest （0.967， 95%CI： 0.936-0.997）， and the sensitivity and specificity were 90.38% and 92.11%， respectively.ConclusionThe decreased expressions of exosomes SOCS1， SP140 and CacyBP in peritoneal dialysis effluent are related to PF， and the combination of these three indexes has a good diagnostic value for PF.